Meaning in the margins: Tracing global blockchain markets in local configurations - Alex Preda; Julie Valk; Ruowen Xu (economic sociology. perspectives and conversations, 2022)
We started writing this a few days after Alex returned from ethnographic fieldwork in Hong Kong. This research trip required being on the road for two months, first doing a washout period in Bucharest, followed by quarantine in Hong Kong, then finally fieldwork itself. This was not Alex's first time in Hong Kong, but in fact the sixteenth. The day Alex boarded a flight back to London, another one of us (Ruowen) boarded a flight to Shanghai for an extended period of fieldwork in China. We plan another round in early 2022 in Japan as well, and in the US too, in addition to the ongoing work in London.
Keywords: 300